Dynamic defense decision method for network real-time confrontation - Qiang LENG; Yingjie YANG; Dexian CHANG; Ruixuan PAN; Ying CAI; Hao HU (网络与信息安全学报)
How to implement defense decision based on network external threat is the core problem of building network information defense system.Especially for the dynamic threat brought by real-time attack,scientific and effective defense decision is the key to construct network dynamic emergency defense system.Aiming at the problem of dynamic defense decision-making,firstly a network survivability game model based on attribute attack graph theory is designed.The attack and defense matrix is used to represent the attack and defense strategy and path,and the attack and defense strength and network survivability quantification method are given.Secondly,the single step and the multi-step attack and defense strategy payoff calculation method is proposed,and the defense decision is based on the attack and defensive strategy payoff.Finally,the effectiveness of the defense decision technology is verified through experiments.